An Improved PSO-FCM Algorithm for Image Segmentation. Issue 4 (May 2019) - Peng, Xia; Lin, Yao; Zhang, Li-Hua
Abstract: FCM algorithm is a kind of soft clustering method widely used in image segmentation, but the algorithm is prone to fall into local minimum and sensitive to initial value. In this paper, considering the local and global optimization capabilities, an improved PSO algorithm is proposed. Image segmentation experimental results show that the improved algorithm not only can effectively avoid the local optimal value due to the manual setting of FCM initial value, but also has better accuracy and anti-noise performance than traditional FCM.